A novel 2.5D spectral approach for studying thin-walled waveguides with fluid-acoustic interaction. (15th July 2018) - Romero, A.; Cruz-Muñoz, F.J.; Tadeu, A.; Galvín, P.
Highlights: New spectral 2.5D FEM formulation to study acoustic and solid guided waves. A novel stabilised plate spectral element based on a mixed formulation. A spectral element to solve the Helmholtz equation in 2.5D is proposed. The h-p convergence of the methodology is analysed. A case study regarding a flexible water duct is studied. Abstract: This paper presents a novel formulation of two spectral elements to study guided waves in coupled problems involving thin-walled structures and fluid-acoustic enclosures. The aim of the proposed work is the development of a new efficient computational method to study problems where geometry and properties are invariant in one direction, commonly found in the analysis of guided waves. This assumption allows using a two-and-a-half dimensional (2.5D) spectral formulation in the wavenumber-frequency domain. The novelty of the proposed work is the formulation of spectral plate and fluid elements with an arbitrary order in 2.5D. A plate element based on a Reissner-Mindlin/Kirchhoff-Love mixed formulation is proposed to represent the thin-walled structure. This element uses C 0 approximation functions to overcome the difficulties to formulate elements with an arbitrary order from C 1 functions. The proposed element uses a substitute transverse shear strain field to avoid shear locking effects. Three benchmark problems are studied to check the convergence and the computational effort for different h - p strategies. Accurate results are found with an appropriate combination of element size and order of the approximation functions allowing at least six nodes per wavelength. The effectiveness of the proposed elements is demonstrated studying the wave propagation in a water duct with a flexible side and an acoustic cavity coupled to a Helmholtz resonator.